Assessment of species diversity, biomass and carbon stock of mangrove forests on Belitung Island, Indonesia - HENRI HENRI; ARTHUR MUHAMMAD FARHABY; OKTO SUPRATMAN; WAHYU ADI; SIGIT FEBRIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Henri, Farhaby AM, Supratman O, Adi W, Febrianto S. 2023. Assessment of species diversity, biomass and carbon stock of mangrove forests on Belitung Island, Indonesia. Biodiversitas 24: 6761-6769. Mangroves are highly productive ecosystems that provide important ecosystem services for people and nature, including climate change mitigation. This study analyzed species diversity, biomass value, and estimated carbon stocks in mangrove forest ecosystems on Belitung Island, Indonesia. The data collection method is carried out by creating a linear plot consisting of several circular subplots. Data analysis was carried out to determine the frequency, density, important value index, biomass (above-ground and below-ground biomass), and carbon content. The results of research on mangrove ecosystems on Belitung Island obtained ten species of mangroves dominated by Rhizophora apiculata Blume found in all research sites. The density of mangroves in the four locations (>1,500 trees/ha) is very dense. In contrast, the location in Juru Seberang (1,349 trees/ha) is categorized as moderate because it is the location of previous reforestation. Rhizophora apiculata has an important value index at the tree (161.24%) and sapling (149.24%) levels. Mangroves on Belitung Island have a total biomass value (225.08 t ha-1), estimated carbon content (112.54 t C ha-1), and carbon dioxide (CO2) absorption of 413.02 t CO2 ha-1. Sustainable coastal ecosystem management can significantly reduce carbon emissions from the land use sector and maintain ecosystem services in these coastal habitats, considering Belitung Island as one of the archipelago areas.